Distance Learning Experiences for Slow Learner Students at SMP Muhammadiyah 9 Yogyakarta - Ristiyanti, Sinta (Program Pascasarjana UIN Sumatera Utara, 2024)
All aspects of life have been hampered by the Covid-19 pandemic, including education. Almost every school is closed. Every school must change the way it approaches teaching and learning. Implementing online learning techniques is the decision most likely to be made during the pandemic. Minority groups, such as students with disabilities in the classroom, have been at a disadvantage during the pandemic. Few studies have been conducted on distance learning involving students with disabilities in inclusive educational environments, given that this is a new and challenging situation for everyone involved. This paper attempts to investigate statistics and direct knowledge obtained from the implementation of distance learning in one of the inclusive junior high schools in Yogyakarta. This article is qualitative research using the case study method. Information was taken from SMP Muhammadiyah 9 Yogyakarta teacher, student, and parent interviews. Thematic analysis is used to carry out the analysis approach. This article uses the data collected to discuss the experiences of parents, teachers, and students with disabilities who went through the pandemic's online learning procedure.Pandemi Covid-19 melumpuhkan segala bidang dalam tatanan kehidupan tak terkecuali bidang pendidikan. Hampir semua sekolah ditutup. Setiap sekolah dituntut beradaptasi dalam proses pembelajaran. Pilihan yang paling memungkinkan diambil di masa pandemi adalah dengan menerapkan metode pembelajaran jarak jauh. Dalam kondisi pandemi, kelompok minoritas seperti peserta didik difabel di kelas berada di posisi terbelakang. Dalam kondisi yang baru dan penuh tantangan bagi semua pihak, pembelajaran jarak jauh yang melibatkan peserta didik difabel dalam setting pendidikan inklusif belum banyak diteliti. Tulisan ini berupaya untuk menggali data dan pengalaman penyelenggaraan pembelajaran jarak jauh di salah satu SMP inklusif di Kota Yogyakarta. Tulisan ini merupakan penelitian kualitatif dengan metode studi kasus. Data digali dari wawancara dengan pihak guru, peserta didik, dan orang tua di SMP Muhammadiyah 9 Yogyakarta. Teknik analisis dilakukan dengan analisis tematik. Dengan data yang diperoleh, tulisan ini menggambarkan bagaimana kesiapan serta pengalaman guru, peserta didik difabel, dan orang tuanya dalam melalui proses pembelajaran jarak jauh di masa pandemi.